MARKET PERFORMANCE: THE EFFECT OF INTELLECTUAL CAPITAL AND INTELLECTUAL CAPITAL DISCLOSURE - Mukhtaruddin Mukhtaruddin; Yulia Saftiana; Ely Riani; Emi Yulia Siska; Fadhil Yamaly (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Intellectual Capital is a concept which gives new knowledge-based resources and optimally describes the intangible assets utilized. It enables a company to run its strategies effectively and efficiently without revealing its intangible assets such as knowledge, relationships and image in the financial report. These attributes create differences and describe the company’s future opportunities. The research therefore illustrated how Intellectual Capital (IC) and Intellectual Capital Disclosure (ICD) influenced the Market Performance (MP) by using the purposive sampling method. The data used is secondary which was obtained from 102 service companies listed in the Indonesian Stock Exchange (IDX) and analyzed using the multiple linear regression. The result of this research showed that both IC and ICD influenced the MP. This research indicated that the signal presented by the company through ICD minimized asymmetrical information. This proved that maximum management of the IC gave some added values capable of increasing competitive advantages.